DETECTION OF STAPHILOCOCCUS SP. FROM THE PIG RESPIRATORY TRACT - Purwanti, Makselina Ayu Dwi; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2018)
This research was conducted for the detection of Staphylococcus sp. in the respiratory tract of pigs. Samples differentiated by sex (male pigs and female pigs). A total of 100 nasal swab samples were collected aseptically from pigs showing symptoms of respiratory disease, from pig farms in the area of Badung and Tabanan. All samples were cultured on to Blood Agar for 18-24h at 37°C. Suspected colonies were then Gram staining, primary tests (tested for catalase and oxidase) and series of biochemical tests. Statistical analysis (Chi-square) was performed to explore the differences in positive samples numbers of Staphylococcus sp . isolated between male and female pigs. Of the 100 samples, seven positive samples of Staphylococcus sp . (six of the boars and one from the female pig). Statistically, the number of boars infected with Staphylococcus sp. higher (P<0.01) than with female pigs Staphylococcus species isolated were: Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus saprophyticus, respectively.